2013
DOI: 10.1088/0957-4484/24/48/484009
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic improvement of the PBDTTT-C and PC71BM blend film with mixed solvent for high-performance inverted polymer solar cells

Abstract: Tracing the evolution of the bulk heterojunction structure, a dramatic promotion in the efficiency of polymer solar cells has been obtained in recent years. The active layer morphology of low-bandgap polymer solar cells is one of the critical factors for high-efficiency performance. In the past, the relationship between morphology improvement and the device's characteristics (such as efficiency, fill factor and short-circuit current) in low-bandgap polymer solar cells has been studied intensively with regards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…27,44,45 The interfacial dipole layer is beneficial to increase the built-in field, resulting in the increased V OC of PSCs. [47][48][49] Therefore, the working solvents have a relatively fast volatilization process compared with the DIO additive from the active layers. S7.…”
Section: Resultsmentioning
confidence: 99%
“…27,44,45 The interfacial dipole layer is beneficial to increase the built-in field, resulting in the increased V OC of PSCs. [47][48][49] Therefore, the working solvents have a relatively fast volatilization process compared with the DIO additive from the active layers. S7.…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25] However, the morphology of active layer including narrow band gap polymer is hardly adjusted by thermal annealing treatment due to its poor self-packaging characteristic. 26,27 Recently, Liang et al reported an efficient method to adjust the active layer morphology by adopting mixed solvent approach. 28 Dou et al also reported that the PCE of PSCs was increased to 5.8% from 1.5% by using 1,8-diiodoctane (DIO) as solvent additive based on a blend lm composed of poly{2,6 0 -4,8-di(5-ethylhexylthienyl)benzo[1,2-b;3,4-b]dithiophene-alt-5dibutyloctyl-3,6-bis…”
Section: Introductionmentioning
confidence: 99%
“…CN is another material that has been used as a processing additive, 94,95 but unlike other processing additives such as DIO or ODT, CN is a good solvent for the fullerene derivative (e.g., the solubility of PC 71 BM in CN was reported to be above 400 mg mL −1 ) 81 and is known for being a good solvent for aromatic polymers. 76 In other D:A blends, CN was found to reduce the aggregation of polymers.…”
Section: Case Of Cnmentioning
confidence: 99%